Physiological Changes of Thyroid Hormones in Women with Osteoporosis in Iraq / Basra Province - Almajeed, Mustafa A; Kathim, Sami J (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2021)
Osteoporosis is described as sickness due to fading bone mass and microarchitecture spoilage of bone tissue leads to consolidation bone fragility and increase risk of fracture. The relationship between osteoporosis and thyroid is important by of the skeleton bones in turnout of circulating physical thyroid hormone and TSH condensation to reduced bone mineral loss in osteoporosis patients, also researcher derives that hormone thyroid and TSH scale increased bone resorption, by increase bone mineral deposition. (110) patients female transfer from provincial and civilian habitation, their ages between (55-75) years old, they pay a visit to DEXA station to measure the density. The samples of blood after diagnosis of disease were taken, then the thyroid hormones were gauged by the modern VIDAS automated quantitative device according to the methods which assay serum or plasma. The outcome appeared to decrease significantly (pâ‰¤0.05) in TSH, T3, and T4 in osteoporosis women compared with healthy women, also no significant changes occur between housing status. Thyroid hormones have significant changes in osteoporosis women matched with good health women in Iraq / Basra province.